EVALUASI PROGRAM PEMBERIAN TABLET FE PADA IBU HAMIL - Ardan Ardan; Devi Savitri Effendy; Asriati Asriati (NHM PRESS, 2022)
Pregnant women with anemia will increase the risk of giving birth to babies with low birth weight, miscarriage, premature birth, risk of bleeding before and/or during delivery which can cause death of the mother and baby. The prevalence of anemia in pregnant women for 2018 is 4.7 % and increased in 2019 by 16.87% which then decreased in 2020 by 12.24%. The prevalence of anemia in pregnant women in North Buton Regency is still high compared to the national target. This research is an evaluative research with a qualitative approach. Determination of informants in this study using purposive sampling and accidental sampling (Snowbal Sampling). The number of samples or respondents in this study were 12 people consisting of key informants and regular informants. The results in the study were the program of giving blood tablets to pregnant women in the working area of ​​the Bone Rombo Health Center, namely this was considered unsuccessful because there were still many pregnant women who felt dizzy due to anemia and cases of bleeding after giving birth.